EFFECT OF KINESIO TAPING ON FUNCTIONAL PERFORMANCE IN FOOTBALL PLAYERS - Dede Baştürk,; Kadir Gökdemir,; Metin Kaya,; Bayram Sönmez Ünüvar,; Halil Taşkin,; Nurtekin Erkmen, (Sport Scientific And Practical Aspects, 2025)
The aim of this study was to investigate the effects of Kinesio Taping on functional performance in football players. Eighteen football players from university team volunteered to participate in the study. Their average age, body weight and height were 22.6 ± 1.64 years old, 70.2 ± 4.31 kg, and 176.0 ± 6.36 cm, respectively. Subjects performed vertical jump, standing broad tests, triple-hop test and agility test with and without kinesio taping. Paired samples t-test was used in comparison of the data obtained after the tests conducted with and without kinesio taping application. It was determined that there was no significant difference between the test performances of the subjects in vertical jump, standing broad jump, standing broad jump with dominant leg, triple-hop test and agility with and without Kinesio taping application (p > 0.05). As a result, it is thought that Kinesio Taping applied on m. quadriceps may not have an effect on increase or decrease muscle of the performance. Kinesio Taping may not limit the functional performance in football players.